Isolated retrobulbar optic neuritis after Klebsiella pneumoniae infection: A rare case report and literature review - Qing Wang; Shijie Duan; Shikun Deng; Shenghui Yu (IDCases)
A new invasive Klebsiella pneumoniae liver abscess syndrome (IKPLAS) has been described. It is often described as primary liver abscess and metastatic infection in multiple systems. Patients often develop endogenous endophthalmitis (EE), when the infection affects the eyes. Isolated optic neuritis (ON) is an unusual manifestation of Klebsiella pneumoniae (K. pneumoniae) infection associated ocular complications. We report a rare case of isolated retrobulbar optic neuritis in a 33-year-old young man on the 4th day of admission with severe pneumonia as the first symptom. Cerebrospinal fluid (CSF) analysis showed higher protein levels (1.12 g/l) but aquaporin-4 (AQP4) & myelin oligodendrocyte glycoprotein (MOG) antibodies were negative. Pulse therapy with intravenous methylprednisolone (1 g daily for 3 days, followed by tapering for a total of 2 months) and immunoglobulin (37.5 g daily for 5 days) was effective on his ON. We suggest that this was a form of para-infectious optic neuritis (PON) triggered by K. pneumoniae infection. K. pneumoniae antigens induced para-infectious demyelination of the optic nerve may be involved in visual impairment.